2010
DOI: 10.4049/jimmunol.0904084
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of CCL1 Inhibits T Regulatory Cell Suppressive Function Enhancing Tumor Immunity without Affecting T Effector Responses

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 56 publications
6
71
0
Order By: Relevance
“…+ T cells to the tumor site [19][20][21][22]42]. These findings are in accordance with our observation that lipoplex induced infiltration of NK and CD8 + T cells into the tumor, thereby resulting in antitumor activity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…+ T cells to the tumor site [19][20][21][22]42]. These findings are in accordance with our observation that lipoplex induced infiltration of NK and CD8 + T cells into the tumor, thereby resulting in antitumor activity.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, we explored the effect of CpG4531 and lipoplex treatments on the mRNA expression profiles of various chemokines (CCL1, CCL3, CXCL1, and CXCL10) in the tumor tissue. These proinflammatory chemokines regulate intratumoral trafficking of leukocytes, including T cells and NK cells, and inhibit tumor growth [19][20][21][22]. As shown in Fig.…”
Section: Lipoplex Enhanced the Intratumoral Infiltration Of Nk And Cd8mentioning
confidence: 99%
“…This study also identified that the genes which encode the T-lineage cell markers and chemotaxis molecules, such as CD7, CCL1, and CXCR3, are upregulated in the wild-type Helios-1 overexpressed Jurkat cells, whereas the B-lineage cell marker CD79a are downregulated. It has been reported that regulatory T-cells initiate recruitment and suppressive function via a CCL1 dependent pathway (23,24). In addition, the CXCR3 signaling directly induces the mobilization and recruitment of Tregs (25).…”
Section: Discussionmentioning
confidence: 99%
“…129 In ovarian cancer models, the infusion of NKG2D-CARexpressing T cells increased the number of host CD4+ and CD8+ T cells at the tumour site in a CXCR3-dependent manner and increased the number of antigen-specific host CD4+ T cells in the tumour and draining lymph nodes. This showed that adoptively transferred T cells recruit and activate endogenous T cells.…”
Section: Modulation Of the Local Chemokine Milieu To Recruit T Cells mentioning
confidence: 99%